Design and construction of uninterruptible power supply system - Tan, Kay Jiunn. (2009)
Uninterruptible power supply system has become an important part of our life and is greatly used by the general public. The more common ones are the computer uninterruptible power supply system and its main function is to restore electricity when there is power outage. Major companies which require data storage such as banks and telecommunication industries spend a lot of money on uninterruptible power supply system and are heavily dependent on it so that no important information is lost due to power shortage.